Notas sobre aves de colombia (1962)
We present some notes concerning principally with the distribution and systematic position of some species or subspecies of birds from the valley of the Magdalena river in the Departments of Santander, Cundinamarca and Tolima in Colombia.  The field-work in Santander was carried under the auspices of the Instituto Carlos Finlay of Bogotá, Colombia.